Reports of His Death Have Been Greatly Exaggerated - Goodhand, James ([Place of publication not identified] : Mira Books, 2025)
A lifetime ago, Ray "Spike" Thorns was a well-regarded caretaker on a boarding school's grounds. These days, he lives the life of a recluse in a house rammed with hoarded junk, alone and disconnected from family or anyone he might have at one time considered a friend. When his next-door neighbor drops dead on Spike's doorstep, a case of mistaken identity ensues: according to the police, the hospital, the doctors--everyone--Spike is dead. Spike wants to correct the mistake, really he does, but when confronted with those who knew him best, he hesitates, forced to face whatever impression he's left on the world. It's a discovery that brings him up close to ghosts from his past, and to the only woman he ever loved"--.
new book 2025 summer.
Keywords: Life change events; Mistaken identity; Recluses; Opportunity; Loneliness; Absence and presumption of death